2019
DOI: 10.11604/pamj.supp.2019.33.2.16848
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening acute flaccid paralysis surveillance post Ebola virus disease outbreak 2015 - 2017: the Liberia experience

Abstract: Introduction Liberia remains at high risk of poliovirus outbreaks due to importation. The country maintained certification level acute flaccid paralysis (AFP) surveillance indicators each year until 2014 due to Ebola outbreak. During this time, there was a significant drop in non-polio AFP rate to (1.2/100,000 population under 15 years) in 2015 from 2.9/100, 000 population in 2013, due to a variety of reasons including suspension on shipment of acute flaccid paralysis stool specimen to the polio r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The proportion of districts with target stool adequacy rate significantly increased between 2015 and 2020, with mean stool adequacy rate in the study period being higher than the recommended target of 80%. This finding is in line with what was found in other countries including Ethiopia [ 17 ], some eastern and southern African countries [ 22 ], and Liberia [ 28 ]. There were sub-regional variations in terms of stool adequacy.…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of districts with target stool adequacy rate significantly increased between 2015 and 2020, with mean stool adequacy rate in the study period being higher than the recommended target of 80%. This finding is in line with what was found in other countries including Ethiopia [ 17 ], some eastern and southern African countries [ 22 ], and Liberia [ 28 ]. There were sub-regional variations in terms of stool adequacy.…”
Section: Discussionsupporting
confidence: 93%
“…African countries [23], and Liberia [33], our ndings showed that it is even more critical that the AFP surveillance system should be strengthened in Niger. Niger should analyse routine AFP index to identify any subnational gaps to guide AFP activities and thereby minimize the consequences of any new virus introduction.…”
Section: Discussionmentioning
confidence: 80%
“…The demand for quality and real-time information using geographic information systems (GIS) and other technologies by policymakers at levels by different stakeholders in the polio eradication programme is increasing and several approaches and tactics had been adopted to meet these demands. Digital technologies had proven to have supported positively the polio eradication programme through enhancing surveillance performance [ 7 - 10 ], support the implementation of real-time supplemental immunisation activities (SIAs) [ 11 - 13 ], use of mobile phones to support polio vaccination [ 14 ], tracking vaccination teams during the conduct of polio campaigns in northern Nigeria [ 15 ], creating maps using a geographical information system to aid microplanning for enhanced close supervision [ 16 ], the use of mobile phones short text messages (SMS) for community mobilization and conduct of surveys to support polio campaigns [ 17 , 18 ], use of real-time data transmission approach in campaign monitoring [ 19 ], the use of mobile data collection tools in the conduct of lot quality assurance sampling (LQAs) to support post-campaign monitoring [ 20 ] and leveraging the use of mobile technology in support of polio post-campaign evaluation [ 21 ] among others.…”
Section: Introductionmentioning
confidence: 99%